Scientific Basis of the Effect of Groundwater Sources for Irrigation in Current Natural Conditions on the Development of Crops - Аkhmedov Sharif Ruzievich; Tursunov Ikrom Numon ugli; Amanova Zulfizar Uktamovna; Sultonov Rustamjon Subhonali ugli; Ulmasov Suhrob Khurshid ugli (Zien Journals, 2022)
In the Bukhara oasis, the use of low-mineral groundwater for irrigation and the use of waterefficient irrigation in the care of autumn cereals with the introduction of 50 kg of hydrogel crystals per hectare, seasonal irrigation, positive changes in the growth and development of grain, seasonal irrigation 3800- 4000 m3 / ha..
Keywords: irrigation sources; underground water; temperature; water consumption regime